Is intent to migrate irregularly responsive to recent German asylum policy adjustments? - Bernd Beber; Cara Ebert; Maximiliane Sievert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
We investigate the extent to which asylum policies that aim to deter individuals from migrating irregularly in fact do so. We specifically consider effects of Germany's recent and high-profile asylum policy adjustments, which include accelerated asylum decision processes, the prospect of asylum processing outside of Europe, the introduction of a payment card to replace cash benefits, and an extended waiting period for native-level benefits. In order to estimate effects of these policy measures on irregular migration intent, we implement a conjoint experiment with 989 men aged 18-40 in four cities in Senegal, a population of most-likely migrants in a country where irregular migration to Europe is highly salient. We find that offshoring the asylum process significantly and substantially lowers irregular migration intentions across nearly all types of subjects. Extending the waiting time for native-level benefits only has a small, marginally significant effect on intent, and no effect among the poorest subjects and those that are most motivated to migrate internationally. Neither reducing asylum processing times nor replacing cash benefits with a payment card significantly alters intentions. We note that the presence or absence of an effect does not resolve political and normative questions concerning these policies, which are beyond the scope of this particular study. – – Wir untersuchen, inwieweit asylpolitische Maßnahmen, die darauf abzielen, Menschen von irregulärer Migration abzuhalten, dies auch tatsächlich tun. Wir untersuchen insbesondere die Auswirkungen der jüngsten und öffentlichkeitswirksamen Anpassungen der deutschen Asylpolitik, zu denen beschleunigte Asylentscheidungsverfahren, die Aussicht auf Asylverfahren außerhalb Europas, die Einführung einer Bezahlkarte als Ersatz für Barleistungen und eine verlängerte Wartezeit für Analogleistungen gehören. Um die Auswirkungen dieser politischen Maßnahmen auf die Absicht der irregulären Migration zu schätzen, führen wir ein Conjoint-Experiment mit 989 Männern im Alter von 18 bis 40 Jahren in vier senegalesischen Städten durch, also mit einer Bevölkerungsgruppe, in der irreguläre Migration nach Europa präsent ist. Wir stellen fest, dass die Verlagerung des Asylverfahrens die Absicht zur irregulären Migration bei fast allen Subjekttypen signifikant und erheblich senkt. Die Verlängerung der Wartezeit für Analogleistungen hat nur einen kleinen, marginal signifikanten Effekt auf Migrationsabsichten, und keinen Effekt bei den ärmsten Personen und denjenigen, die am meisten motiviert sind, international zu migrieren. Weder die Verkürzung der Bearbeitungszeiten für Asylanträge noch die Ersetzung von Geldleistungen durch eine Bezahlkarte haben einen signifikanten Einfluss auf die relevante Migrationsabsicht. Wir weisen darauf hin, dass das Vorhandensein oder Nichtvorhandensein eines Effekts politische und normative Fragen in Bezug auf diese Maßnahmen nicht löst.
Keywords: F22; J61; K37; 330; Asylum policy; irregular migration; conjoint experiment